Mitochondrial respiration of adipocytes differentiating from human mesenchymal stem cells derived from adipose tissue - Kladnická, I; Čedíková, M; Kripnerová, M; Dvořáková, J; Kohoutová, M; Tůma, Z; Müllerová, D; Kuncová, J (Physiological research, 2019)
Burden of obesity is increasing in the contemporary world. Although multifactorial in origin, appropriate mitochondrial function of adipocytes emerges as a factor essential for healthy adipocyte differentiation and adipose tissue function. Our study aimed to evaluate mitochondrial functions of human adipose-derived mesenchymal stem cells committed to adipogenesis. On days 0, 4, 10, and 21 of adipogenesis, we have characterized adipocyte proliferation and viability, quantified lipid accumulation in maturing cells, performed qualitative and quantitative analysis of mitochondria, determined mitochondrial respiration of cells using high-resolution respirometry, and evaluated mitochondrial membrane potential. In the course of adipogenesis, mitochondrial oxygen consumption progressively increased in states ROUTINE and E (capacity of the electron transfer system). State LEAK remained constant during first days of adipogenesis and then increased probably reflecting uncoupling ability of maturing adipocytes. Citrate synthase activity and volume of mitochondrial networks increased during differentiation, particularly between days 10 and 21. In addition, lipid accumulation remained low until day 10 and then significantly increased. In conclusion, during first days of adipogenesis, increased mitochondrial respiration is needed for transition of differentiating cells from glycolytic to oxidative metabolism and clonal expansion of preadipocytes and then more energy is needed to acquire typical metabolic phenotype of mature adipocyte.
Keywords: Mitochondria; adipogeneze; Cell Respiration; buněčné dýchání; Adipocytes; metabolismus lipidů; kultivované buňky; tukové buňky; lidé; ženské pohlaví; Adipogenesis; Humans; Lipid Metabolism; membránový potenciál mitochondrií; Cells, Cultured; Female; Mesenchymal Stem Cells; Membrane Potential, Mitochondrial; mitochondrie; mezenchymální kmenové buňky